2008
DOI: 10.1177/1934578x0800300810
|View full text |Cite
|
Sign up to set email alerts
|

Surface Flavonoids in Catalpa Ovata, Greyia Sutherlandii and Paulownia Tomentosa

Abstract: Exudate flavonoids have been found on the green fruits of Catalpa ovata (Bignoniaceae) and Paulownia tomentosa (Scrophulariaceae) and on the leaf surfaces of Greyia sutherlandii (Melianthaceae) and Paulownia tomentosa, respectively. The flavonoid aglycones are mostly flavone and flavonol methyl ethers, including some rare natural products. Several flavanones and 2 dihydrochalcones have also been detected, the flavanones produced by Paulownia being geranylated products. The occurrence of exudate flavonoids on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In a recent paper, reporting on exudate flavonoids occurring on green fruits of Catalpa ovata and Paulownia tomentosa [6], it was suggested that more attention should be paid to the localization of flavonoids on (unripe) fruits, which is underlined by our present results. Current results also indicate that organ specific diversification of exudate flavonoid profiles may occur occasionally.…”
Section: No 2 211 -212supporting
confidence: 63%
“…In a recent paper, reporting on exudate flavonoids occurring on green fruits of Catalpa ovata and Paulownia tomentosa [6], it was suggested that more attention should be paid to the localization of flavonoids on (unripe) fruits, which is underlined by our present results. Current results also indicate that organ specific diversification of exudate flavonoid profiles may occur occasionally.…”
Section: No 2 211 -212supporting
confidence: 63%
“…Leaves, green immature fruit (Wollenweber et al 2008) Antimicrobial activity, poor antifungal effect (Omosa et al 2014); low antimicrobial activity, low toxicity against human lymphocytes and monocytes, antioxidant/antiinflammatory activity (Martini et al 2004;Pelzer et al 1998); low affinity to acetylcholinesterase (Remya et al 2012); low inhibitory effect on NO production in RAW264.7 cells (Sudsai et al 2013); no activity against HSV-1, low toxicity against Vero cells (Tian et al 2009); no antioxidant activity (Takamatsu et al 2003); no trypanocidal activity (Grael et al 2000); activity against lipid peroxidation in rat liver microsomes (Yun et al 2000); cytotoxicity against TK-10, MCF-7 and UACC-62 cells (Lopez-Lazaro et al 2000); no inhibition of glycolysis in various tumor cells (Suolinna et al 1975 ,4 0 -Trimethylquercetin (7) Thrombin inhibition (Shi et al 2012); inhibition of IL-4 synthesis in basophils (Hirano et al 2006); weak trypanocidal activity (Jordao et al 2004); weak inhibition of NO production in LPS-activated mouse peritoneal macrophages (Matsuda et al 2003); weak inhibition of degranulation of RBL-2H3 cells (Mastuda et al 2002);…”
Section: /K ?mentioning
confidence: 99%
“…NMR Spectroscopic Data (400 MHz, MeOD) for Tomentodiplacones L (1) and M (2) and Tomentodiplacol B(3) …”
mentioning
confidence: 99%
“…In particular, C -geranyl flavonoids obtained from P. tomentosa fruits have become the focus of phytochemical research because of their wide spectrum of biological activities. So far, 38 geranylated and two prenylated flavonoids have been isolated from P. tomentosa . Twenty-six of these C -geranyl flavonoids possess a side-chain modified by oxidation, reduction, or cyclization. The significant bioactivities of these geranylated flavonoids have been investigated mainly using antibacterial, cytotoxic, antiphlogistic, or antioxidant assays. , ,− …”
mentioning
confidence: 99%